Reestructuración técnico administrativa para la empresa Vm Cargo Services S.A.S. (2019)
The following degree work is done for the company Vm Cargo Services S.A.S. in the city of Bogotá DC, in order to carry out a technical-administrative restructuring, in which it is possible to observe a diagnosis through a PESTAL analysis at the territorial level, that is to say in Bogotá DC, an analysis of the subsector through the matrix DOFA, as it allows us to observe the threats, opportunity, weaknesses and strengths that the company has in front of its customers, competitors, suppliers, among others. When determining the diagnosis, the technical study will be followed in which industrial engineering tools will be used to establish worker times and movements, the processes that the Vm Cargo Services SAS company uses to carry out its courier services, the optimal suppliers will also be evaluated , all in order to stipulate a continuous improvement to its processes. In the third instance is the administrative study that allows to know the organizational structure that the company contains through a manual of functions, organizational charts, strategic planning, salary and payroll studies. Finally, the financial study is established to verify how viable are the proposals presented in the degree work to be implemented in the company.